Innovating for cleaner skies: A study on the impact of China's national innovation demonstration zones on urban air quality from the perspective of energy consumption - Hao Zhu; Songyu Jiang (Energy Strategy Reviews, 2024)
In pursuit of innovation-driven green development, effectively leveraging innovation policies for environmental betterment has emerged as a pivotal challenge in China's sustainable development trajectory. Investigating 287 Chinese cities from 2010 to 2020, this study adopts the pilot initiative of National Innovation Demonstration Zones (NIDZs), a cornerstone of China's regional innovation strategy, as a quasi-natural experimental setup. Utilizing a double machine learning method, we probe into the implications of implementation National Innovation Demonstration Zones pilot policy on urban air quality, its underlying mechanisms, and the regional heterogeneity in policy outcomes. The empirical evidence underscores that implementation National Innovation Demonstration Zones pilot policy significantly bolster urban air quality, a result that persists endogenous controls and rigorous robustness checks. Mechanistically, setting up the National Innovation Demonstration Zone can significantly curb the deterioration of urban air quality by reducing the total energy consumption of the whole society, including the reduction of total electricity consumption, the use of manufactured gas and natural gas, and the consumption of liquefied petroleum gas. Regionally, the Southeast demonstrates enhanced efficacy in mitigating air quality degradation and PM2.5 concentration, whereas the Northwest sees pronounced reductions in urban carbon dioxide emissions following the implementation National Innovation Demonstration Zones pilot policy.